Behaviour of Beam-Column Joints Retrofitted with High Strength Fiber Reinforced Concrete at Varying Levels of Corrosion Damage - Dangwal, Shubham (My University, 2024)
The exterior beam-column joints (BCJs) within a moment-resisting frame must possess high resistance against shear forces which goes hand in hand with the ability to withstand large deformations when subjected to seismic loading. The failure of RC framed structure can occur not only due to mechanical reasons but from environmental factors also. Corrosion is a prime example of the premature deterioration of RC structures by degrading strength and ductility of reinforcement. Corrosion leads to the deposition of rust on the surface of reinforcing steel which causes a volumetric expansion in the reinforcing bars. A volume increment of approximately six to ten times that of the original steel bar can be experienced due to the formation of hydrated ferric oxide (rust) (Fe2O3.xH2O). Due to this volume expansion at the concrete/steel interface, cracks can be experienced on the concrete surface once the concrete tensile strength surpasses. Over a significant time, corrosion can lead to a drastic reduction in rebar cross- sectional area. A deterioration of concrete and steel bond is also experienced due to the de- scaling of reinforcing bars. These phenomena can severely degrade the energy dissipation and load-carrying capacity of a corrosion-affected structure upon exposure to extreme loading conditions like an earthquake, resulting in catastrophic failure. The present experimental study is categorized into two parts where total 16 Exterior Beam- Column joint specimens were cast and tested. In the first part, the seismic performance of Exterior BCJ specimens subjected to corrosion damage at different levels was investigated. Two different reinforcement detailing were adopted for BCJ (i.e. non-seismic and seismic). The specimens were subjected to accelerated corrosion at three levels, finalized with the help of pilot specimens. The corrosion was targeted at the junction of beam-column. Thereafter, performance of control and corroded non-seismically and seismically detailed specimens were reported and compared through various seismic parameters. The post-peak behaviour, damage progression at higher displacements, and the ultimate failure modes of corrosion- damaged specimens were covered extensively. After assessing the performance degradation in corrosion-damaged specimens, the rehabilitation of the specimens was a requirement to ensure safety within their service period. Therefore, the second part of the experimental study focused on retrofitting of the corrosiondamaged specimens was performed using High Strength Fiber Reinforced Concrete (HSFRC). A new retrofitting scheme was proposed to address the treatment of the corrosion- damaged reinforcing bars prior to the application of retrofitting material. The area to be retrofitted was finalized by visually monitoring the corroded reinforcement cage of the pilot specimen. The retrofitting material i.e. HSFRC was developed in the laboratory after performing several trials focusing on workability and strength. The retrofitted specimens were tested under reverse cyclic loading and the seismic performance was evaluated using similar seismic parameters to first part of the study, so as to generate a comparison between corrosion-damaged non-retrofitted and retrofitted specimens. From the first part of the experimental study, it was concluded that seismically detailed specimens having different levels of corrosion show superior performance when compared to non-seismically detailed specimens. In general, the pitting effect on reinforcing bars leads toward bar fracture under repetitive loading ultimately resulting in reduced ductility. The ultimate failure mode shifted from shear failure at the junction of uncorroded BCJ to flexural failure at beam surface (having fractured reinforcing bars) under corrosion damage. The second part of the experimental study showed the significantly improved performance of corrosion-damaged retrofitted specimens in terms of maximum load-carrying capacity, stiffness, energy dissipation, and ductility. Due to the superior mechanical properties of HSFRC, the delay in the fracture of severely pitted reinforcing bars was experienced. Moreover, the damage progression during the cyclic loading was due to the presence of hybrid steel fibers providing the crack bridging mechanism. The results obtained from the first part of the experimental study were numerically validated for all the tested specimens. Three-dimensional non-linear finite element (FE) models were prepared for all the specimens in the software. The numerical models were validated with the results obtained from the experimental study. It was noticed that the peak load-carrying capacity values from numerical simulations agreed acceptably with the experimental values. After the validation, the load-carrying capacity and damage progression of uncorroded and corroded specimens were captured and evaluated with the help of parameters such as Von Mises stress levels and Plastic Strain magnitude (PEMAG).
Keywords: Corrosion Damage; Seismic Performance; Numerical Modeling of Corrosion; Seismic Detailing; Seismic Behaviour; Exterior Beam-Column Joint; Accelerated Corrosion; Cyclic Loading